Interrelation Between Online Instruction and E-Resources in Higher Education (Orchid Academia Siraha, 2023)
To measure the interrelationships between online instruction and e-resources in higher education is the objective of this study. Four hundred students who are studying for a master degree in Kathmandu Valley are randomly assigned. A correlational research design is applied within the nonexperimental study with a positivist philosophical background. Data are collected once through a semi-structured questionnaire. Relationships were identified using chi-square and logistic regression through Stata 14. The results show that the majority of students have limited access to e-resources. Less than one-third of students have utilized online resources. Students' satisfaction and perception of effective online instruction were more likely to utilize e-resources. The study concludes that online modes of instruction have limited success in utilizing online resources. The majority of students have limited access to e-resources and mainly depend on printed materials. The study suggests that practical-based training for utilizing online resources should be provided to enhance proficiency in technology and awareness of e-resources.